Effectiveness of antioxidants in refined, bleached and deodorized palm olein - Augustin, M. A.; Berry, S. K. (Wiley, 1983)
The addition of antioxidants butylated hydroxytoluene (BHT), propyl gallate (PG), tertiary butylhydroquinone (TBHQ), dilaurylthiodipropionate (DLTDP), and trihydroxybutyrophenone (THBP) at a level of 200 ppm to refined, bleached and deodorized (RBD) palm olein resulted in the retardation of the oxidative deterioration of the oil when stored at 60 C for a period of 10 weeks. The extent of oxidative deterioration was determined by measuring the peroxide and anisidine values and E 1 cm 1% at 232 nm and 268 nm of the oil. Butylated hydroxyanisole (BHA) proved to be a relatively ineffective antioxidant, whereas TBHQ afforded the most protection for the RBD olein.